Quotidiano dos mercadores portugueses em Bruges no século XV - Miranda, Flávio (2022)
The study of merchants' daily life has been following different approaches, which focus on their socioeconomic activities in urban environment (Murray 2005), the places of interaction and rest (Constable 2003), the strategies used for conflict management (Miranda & Wubs-Mrozewicz 2017), and their role as rural landowners (Dyer 2012). Each one of these approaches fills a void in our current knowledge about the life, the work, the social relations, and institutional commitments these individuals had as traders, migrants, diplomats, and producers. This article researches the daily life and social interactions of the Portuguese merchants in fifteenth-century Bruges, examining the places of socioeconomic interaction, the bonds of merchant trust established between locals and foreigners, the evidence on family relations, and the type of conflicts in Fleming territory. The civil sentences, preserved in Bruges's city archive, provide the empirical foundation of this study, which uses, whenever possible, sources from Portugal and other European countries to establish comparative connections. It proposes a methodological division between atypical collective events and atypical individual events, and it argues that the latter allowed for the development of Portuguese-Fleming commercial relations.